Rock Wettability Characteristics Of Some Indonesian Limestones Case Study: Baturaja Formation - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2011)
Rock wettability plays a very important role in affecting various rock physical properties such as relative permeability and capillary pressure. Common practice at present is that carbonate rocks are assumed to be preferentially oil wet in nature. This assumption may prove fatal since the need of true knowledge over the real wettability for one’s carbonate reservoir is often neglected, and wettability aspect in reservoir modeling is in turn based on assumption. To prove over reliability of the assumption a study is carried out using information from 350 core samples taken from Baturaja Formation. The choice for the Baturaja limestone is basically based on the fact that it is a mature productive rock formation and its extensive spread into three of the most productive sedimentary basin in Indonesia, Northwest Java Basin, South Sumatra Basin, and Sunda Basin. The study proves that the assumption of the generally oil wet limestone does not apply for Baturaja limestone. The Baturaja limestone tend to exhibit, quantitatively, equality in their tendency towards oil wettability and water wettability and leave some proportion to neutral or mix wettability as well. However, when a more detailed comparison is made results show that qualitatively the limestone are indeed more inclined to oil wettability than water wettability even though this finding is insufficient to support a conclusion that the Baturaja limestone are specifically oil wet. Other finding from comparison with past studies also shows that limestone may behave in the way sandstones do. Both limestone and sandstones may vary in the same way and no assumption over their preferential wettability is justified without direct measurements. Wettability alteration as the result of hot core cleaning following the widely accepted standard procedure is also strongly indicated. It is therefore concluded that the practice has to be abandoned for a better and reliable laboratory testing results.